Communication Ethics of Generation Z and Millennial Generation on Tiktok Social Media - Rizky Aulia, Muhammad Mirza; Maylanny Christin (JOM, 2024)
Problems often faced in the context of social media in Indonesia include the spread of fake news (hoaxes), hate speech, cyberbullying, and privacy violations. TikTok's popularity among Generation Z and Millennials makes it an ideal platform to study how these generations understand and apply communication ethics in the digital era. The research method used is a descriptive qualitative research method. Overall, this study shows that both Millennials and Generation Z have different understandings and applications of communication ethics, but both recognize the importance of ethical principles in communication on social media. The integration of communication ethics theory with practice in the field provides valuable insights into how ethics can be applied and maintained on platforms such as TikTok. This study reveals the differences in views between Millennials and Generation Z regarding communication ethics on TikTok, as well as how these ethics are operationalized and their impact on social interactions.